Peran National Resource Defence Council (NRDC) Dalam Melestarikan Lingkungan Laut Di Amerika Serikat - Cory Kusuma Purnamasari (Jurusan Ilmu Hubungan Internasional, 2015)
This thesis discusses the role of the Natural Resources Defense Council (NRDC) in preserving the marine environment in the United States. The US itself is a country that has a large sea area and the economy that comes from the sea is quite high and influential. The presence of sea damage that occurred long ago until now have hindered the surrounding ecosystem. Environmental issues include: sewage, oil spills, garbage, overfishing, ocean acidification, sea water content of the poor. The existence of the sea issues attract the federal government to make a policy, not only the government but activists and environmental groups also help preserve the marine environment in the US. Environmental organizations that becoming a major role in this thesis is NRDC. Their roles in preserving the ocean in the US include: catalyzing changes in the system, the monitoring service programs, and implementation services. In this thesis also discussed about the obstacles and achievements NRDC in doing any roles in the US.